Effects of weight loss through dietary intervention on pain characteristics, functional mobility, and inflammation in adults with elevated adiposity - Ward, Susan J.; Coates, Alison M.; Carter, Sharayah; Baldock, Katherine L.; Berryman, Carolyn; Stanton, Tasha R.; Yandell, Catherine; Buckley, Jonathan D.; Tan, Sze-Yen; Rogers, Geraint B.; Hill, Alison M. (Frontiers in Nutrition, 2024)
The relationship between adiposity and pain is complex. Excess weight increases the risk for chronic musculoskeletal pain (CMP), driven by increased biomechanical load and low-grade systemic inflammation. Pain limits physical function, impacting energy balance contributing to weight gain. The primary aims of this study were to profile pain characteristics in participants with overweight or obesity and determine if weight-loss through dietary-induced energy-restriction, and presence of CMP, or magnitude of weight loss, was associated with changes in adiposity, pain, functional mobility, and inflammation.Methods: This was a secondary analysis of data from adults (25-65 years) with overweight or obesity (BMI, 27.5-34.9 kg/m 2 ) enrolled in a 3-month, 30% energy-restricted dietary intervention to induce weight loss (January 2019-March 2021). Anthropometric measures (weight, waist circumference and fat mass), pain prevalence, pain severity (McGill Pain Questionnaire, MPQ), pain intensity (Visual Analogue Scale, VAS), functional mobility (timed up and go, TUG) and inflammation (high sensitivity C-Reactive Protein, hsCRP) were assessed at baseline and 3-months.Results: One hundred and ten participants completed the intervention and had weight and pain assessed at both baseline and 3months. Participants lost 7.0 ± 0.3 kg, representing 7.9 ± 3.7% of body mass. At 3-months, functional mobility improved (TUG -0.2 ± 0.1 sec, 95% CI -0.3, -0.1), but there was no change in hsCRP. Compared to baseline, Compared to baseline fewer participants reported CMP at 3-months (n = 56, 51% to n = 27, 25%, p <0.001) and presence of multisite pain decreased from 22.7% to 10.9% (p <0.001). Improvements in anthropometric measures and functional mobility did not differ between those presenting with or without CMP at baseline. Improvements in pain were not related to the magnitude of weight loss.Conclusions: Weight-loss was effective in reducing pain prevalence and improving functional mobility, emphasizing the importance of considering weight-loss as a key component of pain management.Clinical trial registration: The primary study was registered on the Australian New Zealand Clinical Trials Registry, ACTRN12618001861246.